TATA LAKSANA KEHUMASAN PEMERINTAH MELALUI KONTEN KAMUS GEN Z - Asyifa, Tsalitsa Rizky Nur; Herawati, Erna; Afrilia, Ufa Anita (Universitas Djuanda, 2025)
The use of information and communication technology in government administration can enhance. The quality of public service. Government communication plays a crucial role in maintaining public trust. Social media enables two-way communication between the government and public. This study aims to understand and analyze the government’s public relations management in effectively conveying public information, particularly through the creation of “Gen Z Dictionary” content by the Public Relation Department of the Communication and Information Technology Office (Diskominfo) of West Java Province. The researcher adopted the POAC theory, which consists of the criteria of planning, organizing, actuating, and controlling. This study employed a qualitative descriptive method, with data collected through observation, interviews, and literature review. The data analysis technique used the Miles and Huberman model. The results of the planning stage included establishing communication themes and objectives, audience mapping, determining the style of message delivery, and selecting social media platforms. In terms of organizing, the West Java Public Relations team has a functionally structured team. For actuating, content creation involves producing short videos uploaded through the Instagram Reels feature. Regarding controlling, the content production team monitors the number of views, comments, interactions (engagement), and audience responses to each published episode and evaluates the content production.